The association between team cohesion and performance: A network analysis of nurses. - Huimin Wei; Simeng Zhang; Wenran Qu; Mengqi Liu; Zeping Yan; Xiaorong Luan (Nursing & Health Sciences, 2024)
Team cohesion, as a necessary condition for the cooperation and development of a team, has been shown to have a strong association with team performance. However, the mechanism of this internal correlation is unclear and more in-depth studies are lacking. The study aimed to explore the complex links between the dimensions of team cohesion and performance in nurses. A total of 1639 practice nurses from 118 nursing teams were included in this cross-sectional study. Data were collected using the Team Cohesion Scale (including consistency of affection, behavior, and cognition) and the Team Effectiveness Scale (including cooperation satisfaction, and task performance). Using network analysis, the team cohesion and performance network was constructed, and the strength and bridge strength of nodes were calculated. The results showed that the edges between team cohesion and performance dimensions were all positively correlated. Cooperation satisfaction and consistency of affection are the core variables in the network. Interventions targeting cooperation satisfaction and consistency of affection need to be developed at the team level to maximize team cohesion and performance among nurses.